IntegraBrasil - Mobile Application Prototype - Pereira, Marcelo (2023)
The paradigm of Society 5.0 assumes the availability of Information and Communication Technologies at the service of People. Given this assumption, the paper presents a prototype that aims to facilitate the dissemination of information from an Association to contribute to the integration of migrants in a Portuguese city, thus disseminating the various services provided to expedite their integration and inclusion. The methodology adopted was Design Science Research given its frequent use in the scientific field of Information Systems to enhance the successive iterations underlying the process of creating the artifact. The main results focus on the relevance of using Information and Communication Technologies as vehicles for improving access to information and thus contributing to the integration of the Brazilian community in the city. The prototype presents a mobile application that allows making available in a generalized way the services of the Casa do Brasil Association in Viseu.